Vitamin B12 Levels in Methamphetamine Addicts - Zhai, Changping; Cui, Ming; Cheng, Xiaodong; Ao, Xiang; Zhao, Tingting; Wu, Wei; Shao, Qun; Ge, Dexue; Song, Hongmei; Qi, Fangzhi; Ling, Qiang; Ma, Mengdi; et al. (Frontiers in Behavioral Neuroscience, 2018)
Object: It has been established that reduced vitamin B12 serum levels are associated with cognitive decline and mental illness. The chronic use of methamphetamine (MA), which is a highly addictive drug, can induce cognitive impairment and psychopathological symptoms. There are few studies addressing the association of MA with vitamin B12 serum levels. This study examined whether the serum levels of B12 are associated with MA addiction. Methods: serum vitamin B12, homocysteine (Hcy), glucose and triglyceride concentrations were measured in 123 MA addicts and 108 controls. In addition, data were collected on their age, marital status, level of education and Body Mass Index (BMI) for all participants. In the patient group, the data for each subject were collected using the Fagerstrom Test for Nicotine Dependence (FTND), the Alcohol Use Disorders Identification Test (AUDIT), and a drug use history, which included the age of onset, total duration of MA use, the number of relapses and addiction severity. Results: Our results showed that MA addicts had lower vitamin B12 levels (p < 0.05) than those of healthy controls, but Hcy levels were not significantly different between the two groups (p >0.05). Serum B12 levels were negatively correlated with the number of relapses in the MA group. Furthermore, binary logistics regression analysis indicated that the B12 was an influencing factor contributing to addiction severity. Conclusion: The findings of this study suggest that some MA addicts might have vitamin B12 deficiency, and serum B12 levels may be involved in the prognosis of MA addiction.